Sistem Kontrol Lampu LED menggunakan Sensor Suara KY-037 Berbasis Arduino Uno - Erwin Darmawan; Muhamad Hilmansyah Susanta (Jurnal Teknologi Komputer dan Informatika, 2026)
The development of electronic technology and embedded systems has encouraged the creation of various automation systems aimed at improving efficiency and convenience in daily life. One of the widely used platforms is the Arduino Uno due to its ease of programming and flexibility. This study aims to design and implement an LED lamp control system based on a sound sensor using Arduino Uno. The system utilizes the KY-037 Sound sensor Module as an input to detect sound, which is then processed by the microcontroller to control an LED as the OUTput. The research method includes system analysis, hardware and software design, implementation, and system testing. The sound sensor detects sound intensity and sends signals to the Arduino, which processes them based on a predefined threshold. If the sound intensity exceeds the threshold, the LED turns on and then turns off after a delay. The test results show that the system performs optimally at a distance of 5–20 cm with a response time of 0.2–0.9 seconds. However, performance decreases at longer distances and in noisy environments due to interference.